2011
DOI: 10.1111/j.1467-9221.2010.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Attractiveness and Candidate Evaluation: A Model of Correction

Abstract: Voters typically evaluate an attractive candidate more favorably than an (otherwise equivalent) unattractive candidate. However, some voters "correct" for the biasing influence of physical appearance. This reduces, eliminates, or even reverses the physical attractiveness effect. Correction occurs when political experts evaluate a political candidate under nondistracting conditions. Under these "high cognitive capacity" conditions, voters primarily correct for physical unattractiveness. However, correction fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 50 publications
2
42
0
1
Order By: Relevance
“…For this study attractiveness is of major importance since another set of results show that attractiveness (or beauty) predicts electoral success (see for example Berggren, Jordahl, & Poutvaara, 2010;Hart, Ottati, & Krumdick, 2011;King & Leigh, 2009;Rosar, Klein, & Beckers, 2008). This is largely in line with findings across other social science disciplines that physical attractiveness relates positively to earnings and generally has positive effects throughout the lifecourse (see for example Hamermesh & Biddle, 1994;Jaeger, 2011).…”
Section: Facial Competence And/or Attractivenesssupporting
confidence: 75%
“…For this study attractiveness is of major importance since another set of results show that attractiveness (or beauty) predicts electoral success (see for example Berggren, Jordahl, & Poutvaara, 2010;Hart, Ottati, & Krumdick, 2011;King & Leigh, 2009;Rosar, Klein, & Beckers, 2008). This is largely in line with findings across other social science disciplines that physical attractiveness relates positively to earnings and generally has positive effects throughout the lifecourse (see for example Hamermesh & Biddle, 1994;Jaeger, 2011).…”
Section: Facial Competence And/or Attractivenesssupporting
confidence: 75%
“…Similarly, knowledgeable and engaged voters are less likely to display appearance-based biases when they vote (Hart et al, 2011;Lenz and Lawson, 2011;Riggle et al, 1992;Shephard and Johns, 2008). This is consistent with the broader literature demonstrating that people are more likely to rely on stereotypes to make judgments about people when there is little or no other relevant information available about the person (Davison and Burke, 2000;Tosi and Einbender, 1985).…”
Section: Influence Of Candidate Weight On Voting Behaviorsupporting
confidence: 81%
“…Previous research has found that people rely less on stereotypes and biases when making judgments about others if they have relevant information about a person (Davison and Burke, 2000;Hart et al, 2011;and Lawson et al, 2009;Riggle et al, 1992;Shephard and Johns, 2008;Todorov et al, 2005;Tosi and Einbender, 1985). In US Senate elections, all voters, at the very least, know each candidate's political affiliation, which is listed on the ballot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, voters in winner-take-all plurality electoral systems are more prone to use candidate appearance as a heuristic device than voters in proportional systems (Stockemer and Praino, 2017); conservative candidates benefit more from their physical appearance than others (Berggren, Jordahl, and Poutvaara, 2017); attractive individuals are considered more knowledgeable and more persuasive (Palmer and Peterson, 2016); and good-looking candidates benefit disproportionately from media exposure (Lenz and Lawson, 2011) and get a "break" when involved in scandals (Stockemer and Praino, 2018). A lot of work has also been done on understanding the underlying mechanism applied by voters (Hart, Ottati, and Krumdick, 2011;Stockemer and Praino, 2015). For complete reviews on the current state of literature, see Berggren, Jordahl, and Poutvaara (2017), (Milazzo and Mattes (2015), and Stockemer and Praino (2017). though, overall, attractive job applicants are evaluated more favorably than less attractive applicants, Watkins and Johnston (2000) find that physical attractiveness has no impact when it comes to high-quality job applications.…”
mentioning
confidence: 99%